Calcium Deposits in the Crayfish, Cherax quadricarinatus: Microstructure Versus Elemental Distribution. (28th January 2016) - Luquet, Gilles; Dauphin, Yannicke; Percot, Aline; Salomé, Murielle; Ziegler, Andreas; Fernández, Maria S.; Arias, José L.
Abstract: The crayfish Cherax quadricarinatus stores calcium ions, easily mobilizable after molting, for calcifying parts of the new exoskeleton. They are chiefly stored as amorphous calcium carbonate (ACC) during each premolt in a pair of gastroliths synthesized in the stomach wall. How calcium carbonate is stabilized in the amorphous state in such a biocomposite remains speculative. The knowledge of the microstructure at the nanometer level obtained by field emission scanning electron microscopy and atomic force microscopy combined with scanning electron microscopy energy-dispersive X-ray spectroscopy, micro-Raman and X-ray absorption near edge structure spectroscopy gave relevant information on the elaboration of such an ACC-stabilized biomineral. We observed nanogranules distributed along chitin-protein fibers and the aggregation of granules in thin layers. AFM confirmed the nanolevel structure, showing granules probably surrounded by an organic layer and also revealing a second level of aggregation as described for other crystalline biominerals. Raman analyses showed the presence of ACC, amorphous calcium phosphate, and calcite. Elemental analyses confirmed the presence of elements like Fe, Na, Mg, P, and S. P and S are heterogeneously distributed. P is present in both the mineral and organic phases of gastroliths. S seems present as sulfate (probably as sulfated sugars), sulfonate, sulfite, and sulfoxide groups and, in a lesser extent, as sulfur-containing amino acids.